Frames, Perspectives, and Mental Spaces in the Case of Criminal Humiliation on Social Media (Complaint-Based Offense) within the Legal Jurisdiction of South Sulawesi: A Forensic Linguistics Investigation - Ferdiansa, Deni; Arimi, Sailal (Institut Agama Islam Negeri Palopo, 2024)
Abstract This study is based on the linguistic expressions used by (NH) addressed to (NA) which allegedly contain insult-type hate speech on Instagram. These linguistic expressions were brought into the legal domain and reported to the Directorate of Special Criminal Investigations, Sub-Directorate V of Cybercrime, Regional Police of South Sulawesi and categorized as a complaint-based offense. This study employs forensic linguistic investigation with the support of cognitive linguistics, aiming to analyze the framing, perspectives, and mental spaces within the linguistic expressions of the reported party (NH) and to determine whether these expressions constitute hate speech in the form of insults. This is a descriptive qualitative study using secondary data obtained from Evidence (E) and Investigation and Interrogation Reports from investigators at the Directorate of Special Criminal Investigations (Ditreskrimsus) of the Regional Police of South Sulawesi, Makassar City. This study reveals six types of frames used by NH to insult NA, including the frame of Islam, sin, prostitute, insult, threat, and insinuation. Based on perspective analysis, three viewpoints were identified: the perspective of the reported party (NH), the complainant (NA), and the investigators (police). The reported party (NH) engaged in hate speech in the form of insults by utilizing perspectives based on identity (religious and personal identity), accusations, and comparisons. Mental space analysis was conducted on four linguistic expressions, yielding two concepts from the blending of mental spaces: the concept of a prostitute and the concept of contradiction. Based on these analyses along with the utterances of seven pieces of evidence with (14) linguistic expressions, it is concluded that the linguistic expressions used by (NH) against (NA) have been proven to violate the Electronic Information and Transaction (ITE) Law Article 27 Paragraph (3) of 2016 and the Indonesian Criminal Code on defamation, Articles 310 and 311. Keywords: frame, perspective, mental space, humiliation, forensic linguistic